Man and Society in the Works of the Marquis de Sade - Dreossi, Norma M. (My University, 1975)
Much has been written on the Marquis de Sade's pessimistic and nihilistic philosophy. His criminal man and his social ethic, based on an absolute egotism, have been accepted as embodiments of the Sadian vision of the ideal toward which humanity must struggle to achieve liberty. It is the contention of this thesis that the Sadian arch-fiends illustrate the failure of this struggle. The thesis attempts to examine the other side of Sade's thought, -- an aspect which has been largely ignored -- in order to show that Sade was primarily seeking the realization of a positive ideal in both his vision of man and society, and also in his definition of liberty. What becomes evident from this analysis is that Sade was very much a part of his age in terms of the problems which concerned him, and in terms of the solutions which he evolved in answer to these problems.
Keywords: Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures